Enhancing the efficacy of low doses of N-acetyl-L-cysteine in mitigating CCl4-induced hepatotoxicity in animal model using physical cold plasma - Masume Farhadi; Farshad Sohbatzadeh; Akbar Hajizadeh Moghaddam; Yasaman Firouzjaei; Cheng Cheng (Ecotoxicology and Environmental Safety)
Liver diseases have become widespread especially due to various factors of modern life. Although the effect of N-acetyl-L-cysteine (NAC) is investigated in the recovery of liver damage, gas plasma therapy can be identified as a promising candidate. Our study aimed to enhance the effectiveness of ineffective doses of NAC in stopping CCl4-induced hepatotoxicity in rats by physical cold plasma. The plasma-treated NAC (PTN) structural changes were investigated through FTIR and LCMS/MS analysis. It was observed that the PTN consists of various chemical bioproducts with different molecular weights. We investigated an ineffective dose of NAC and its parallel effect through the administration of PTN on liver and kidney morphology and several biochemical factors including ALT, AST, and ALP. Additionally, we examined oxidative stress, antioxidant parameters, and glutathione (GSH) levels. Results showed that PTN exhibited greater antioxidant properties and increased GSH levels, contributing to its therapeutic effects. Also, the antioxidant enzymes and oxidative stress activities improved after receiving PTN. It also enhanced histological parameters, although various damages were detected in both liver and kidney tissues after CCl4 injection, PTN remarkably prevented the tissue changes caused by CCl4. PTN could protect against liver damage even at a very low dose of NAC, acting as a prophylactic drug with a high margin of safety for hepatotoxicity.